2021
DOI: 10.3389/fgene.2021.709388
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Variance in Interferon Genes to Disease Severity in COVID-19 Patients

Abstract: The rapid rise and global consequences of the novel coronavirus disease 19 (COVID-19) have again brought the focus of the scientific community on the possible host factors involved in patient response and outcome to exposure to the virus. The disease severity remains highly unpredictable, and individuals with none of the aforementioned risk factors may still develop severe COVID-19. It was shown that genotype-related factors like an ABO Blood Group affect COVID-19 severity, and the risk of infection with SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 111 publications
0
11
0
Order By: Relevance
“…Immune responses in COVID-19 patients of various disease severities have been studied (Lega, Naviglio et al 2020, Chiale, Greene et al 2022, Dadras, Afsahi et al 2022). In general, broad induction of IFN responses and antiviral genes are associated with milder/moderate COVID-19, whereas severe COVID-19 is often characterized by a blunt early IFN responses and elevated proinflammatory cytokine expression in nasopharyngeal mucosa (Kwon, Kim et al 2020, Liu, Li et al 2020, Gozman, Perry et al 2021, Janssen, Grondman et al 2021, Vanderbeke, Van Mol et al 2021). Investigation of how IFN responses are induced by SARS-CoV-2 infection, especially early IFN stimulation in some patients, requires further study.…”
Section: Introductionmentioning
confidence: 99%
“…Immune responses in COVID-19 patients of various disease severities have been studied (Lega, Naviglio et al 2020, Chiale, Greene et al 2022, Dadras, Afsahi et al 2022). In general, broad induction of IFN responses and antiviral genes are associated with milder/moderate COVID-19, whereas severe COVID-19 is often characterized by a blunt early IFN responses and elevated proinflammatory cytokine expression in nasopharyngeal mucosa (Kwon, Kim et al 2020, Liu, Li et al 2020, Gozman, Perry et al 2021, Janssen, Grondman et al 2021, Vanderbeke, Van Mol et al 2021). Investigation of how IFN responses are induced by SARS-CoV-2 infection, especially early IFN stimulation in some patients, requires further study.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have demonstrated that common and rare genetic variants that influence the IFN signaling pathways affect the tendency to develop severe COVID-19. Although the prevalence of the impact is 1–5% in young people (≤60 years of age), this fact should be taken into consideration in elderly people [ 109 , 110 ].…”
Section: Immunosenescence and Inflammaging In The Older Adultsmentioning
confidence: 99%
“…Ramensky et al (2021) discussed targeted sequencing of a set of clinically important genes associated with cardiovascular diseases. Gozman et al (2021) raised important actual problem of the role of genetic variance in disease severity in COVID-19 Patients. This problem is continuing to be actively discussed (Lu et al, 2021).…”
Section: Liu Et Al Consider How Cutaneous Melanoma Involves Erbb Tyrosine Kinase Family Members (Erbb Receptor Family) In Its Progressionmentioning
confidence: 99%
“… Gozman et al (2021) raised important actual problem of the role of genetic variance in disease severity in COVID-19 Patients. This problem is continuing to be actively discussed ( Lu et al, 2021 ).…”
mentioning
confidence: 99%